Evaluation of an Australian Aboriginal model of maternity care: The Malabar Community Midwifery Link Service. Issue 5 (October 2019) - Hartz, Donna L.; Blain, Jessica; Caplice, Shea; Allende, Trudy; Anderson, Susan; Hall, Beverly; McGrath, Leona; Williams, Kate; Jarman, Helen; Tracy, Sally K.
Abstract: Background: The urban-based Malabar Community Midwifery Link Service integrates multidisciplinary wrap-around services along-side continuity of midwifery care for Aboriginal and Torres Strait Islander mothers and babies. Aim: To evaluate the Malabar Service from 1 January 2007 to 31 December 2014. Methods: A mixed method design. Outcomes for mothers of Aboriginal and/or Torres Strait Islander babies cared for at an urban Australian referral hospital by the Malabar Service were compared to mainstream. Primary outcomes are rates of low birth weight; smoking >20 weeks gestation; preterm birth; and breastfeeding at discharge. Malabar outcomes are also compared to national and state perinatal outcomes. Results: The Malabar Service (n = 505) demonstrated similar rates of preterm birth (aOR 2.2, 95% CI 0.96–4.97); breastfeeding at discharge (aOR 1.1, 95% CI 0.61–1.86); and a higher rate of low birth weight babies (aOR 3.6, 95% CI 1.02–12.9) than the comparison group (n = 201). There was a 25% reduction in smoking rates from 38.9% to 29.1%. Compared to national and state populations, Malabar outcomes were better. Women experienced greater psychosocial complexity but were well supported. Malabar Mothers (n = 9) experienced: accessibility, preparedness for birth and cultural safety. Staff (n = 13) identified going 'above and beyond' and teamwork to provide culturally safe care counterbalanced with concerns around funding and cultural support. Conclusions: Dedicated integrated continuity of midwifery care with wrap-around services for Aboriginal and/or Torres Strait Islander mothers is highly valued and is culturally safe. The service is as safe as main stream services and promotes better clinical outcomes compared to national and state outcomes.